Multimodality imaging for the assessment of left ventricular dynsfunction in cardio-oncology. (4th February 2022) - Saraiva, M; Moura, AR; Castilho, B; Veiga, R; Domingues, K; Pitta, ML; Martins, V
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Left ventricular systolic dysfunction (LVD) is a key concern in the context of cardio-oncology (CO). Usually, referral for suspected Cancer therapy-related cardiac dysfunction (CTRCD) is the main challenge, but heart failure with other more common causes, such as ischemic cardiomyopathy can also decompensate during cancer treatment or be diagnosed incidentally during cardiotoxicity echocardiographic (echo) surveillance. Multimodality imaging is essential in these patients in order to better establish aetiology and assure the most appropriate clinical management. Purpose: evaluate clinical impact of multimodality imaging in the clinical management of CO patients. Methods: retrospective study of a population followed in CO consultation. Statistical analysis of demographic, clinical, transthoracic echocardiography (TTE) and cardiac magnetic resonance (CMR) data was made. Results: we included 115 pts, mean age 66.3 ± 10.2 years, 67, 8% female, with mean follow-up of 16.1 ± 12.8 months. About half (56.5%) had breast cancer, followed by gastrointestinal tract (16.5%) and haematological (8, 7%) malignancies, with a significant proportion (32, 2%) with advanced disease. Prevalence of cardiovascular risk factors was high (hypertension in 74.8%, dyslipidaemia in 47%, type 2 diabetes mellitus in 17.4%), but also coronary artery disease (18, 3%) and atrial fibrillation (18.3%). All of them were treated with different types of chemotherapy and 53, 9% of pts with radiotherapy.  At baseline, 13% of pts had a left ventricular ejection fraction (LVEF) under 50% (LVD) assessed by TTE, which increased to 26, 9% (n = 31) after oncological treatment initiation. Of these (n = 31), an ischemic aetiology was found in 32, 3% and non-ischemic in 54, 8%, which was significantly more frequent in patients with CTRCD (OR 2, 7, p = 0, 001). CMR was performed in 45, 2%, mostly in CTRCD cases (p = 0, 012, OR 8, 4), which, apart from LVD, did not show any tissue changes in most patients (p = 0, 026, OR 35). Only one patient with CTRCD (under treatment with trastuzumab and anthracyclines) had subepicardial late gadolinium enhancement, with wall motion abnormalities, suggesting a myocarditis-like mechanism for cardiotoxicity. Conclusion: LVD has a major impact in patients" prognosis, particularly in CO context, where effective oncological treatments can be compromised due heart failure decompensation. Therefore, a thorough clinical evaluation should encompass etiological study in order to provide the most appropriate treatment strategies. Moreover, CTRCD can develop through different physiopathological mechanisms. Thus, multimodality imaging, particularly including CMR evaluation, can have a major role ensuring a good clinical outcome for these patients.